Pendampingan Penyusunan Menulis Teks Berita Bagi Mahasiswa Prodi Bahasa Dan Sastra Indonesia - Ratnawati; Muhammad Akhir; Asri Pratiwi; Justika Sukri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study addresses the problem of limited journalistic writing skills among students of the Indonesian Language and Literature Education Program, particularly in composing structured, factual, and ethical news texts. Many students experience difficulties in applying news values, organizing information based on the 5W+1H principle, and using appropriate journalistic language. The purpose of this study was to provide structured assistance in news text writing and to examine its effectiveness in improving students’ news writing competence. The methodology employed was a mentoring-based training model using a descriptive qualitative and quantitative approach. The participants were university students of the Indonesian Language and Literature Program. The mentoring activities were conducted through workshops, guided practice, group discussions, peer review, and individual feedback sessions. Data were collected through observation, writing tests (pre-test and post-test), and documentation of students’ news texts. The results showed a significant improvement in students’ ability to identify news elements, organize information coherently, apply journalistic language features, and produce accurate and objective news texts. The average post-test scores increased compared to the pre-test results, and students demonstrated higher motivation and confidence in writing news. The study concludes that mentoring in news text writing is effective in enhancing students’ journalistic writing skills and can serve as an alternative model for strengthening writing instruction in higher education.